Swedish surgical outcomes study (SweSOS): An observational study on 30-day and 1-year mortality after surgery. Issue 5 (May 2016) - Jawad, Monir; Baigi, Amir; Oldner, Anders; Pearse, Rupert M.; Rhodes, Andrew; Seeman-Lodding, Helen; Chew, Michelle S.
Abstract : Supplemental Digital Content is available in the text Abstract : BACKGROUND: The European Surgical Outcomes Study (EuSOS) revealed large variations in outcomes among countries. In-hospital mortality and ICU admission rates in Sweden were low, going against the assumption that access to ICU improves outcome. Long-term mortality was not reported in EuSOS and is generally poorly described in the current literature. OBJECTIVE: To describe the characteristics of the Swedish subset of EuSOS and identify predictors of short and long-term mortality after surgery. DESIGN: An observational cohort study. SETTING: Six universities and two regional hospitals in Sweden. PATIENTS: A cohort of 1314 adult patients scheduled for surgery between 4 April and 11 April 2011. MAIN OUTCOME MEASURES: 30-day and 1-year mortality. RESULTS: A total of 303 patients were lost to follow-up, leaving 1011 for analysis; 69% of patients were classified as American Society of Anesthesiologists' physical status 1 or 2, and 68% of surgical procedures were elective. The median length of stay in postanaesthesia care units (PACUs) was 175 min (interquartile range 110–270); 6.6% of patients had PACU length of stay of more than 12 h and 3.6% of patients were admitted to the ICU postoperatively. Thirty-day mortality rate was 1.8% [95% confidence interval (CI) 1.0–2.6] and 8.5% (CI 6.8–10.2) at 1 year ( n = 18 and 86). The risk of death was higher than in an age and sex-matched population after 30 days (standardised mortality ratio 10.0, CI 5.9–15.8), and remained high after 1 year (standardised mortality ratio 3.9, CI 3.1–4.8). Factors predictive of 30-day mortality were age, American Society of Anesthesiologists' physical status, number of comorbidities, urgency of surgery and ICU admission. For 1-year mortality, age, number of comorbidities and urgency of surgery were independently predictive. ICU admission and long stay in PACU were not significant predictors of long-term mortality. CONCLUSION: Mortality rate increased almost five-fold at 1 year compared with 30-day mortality after surgery, demonstrating a significantly sustained long-term risk of death in this surgical population. In Sweden, factors associated with long-term postoperative mortality were age, number of comorbidities and surgical urgency.